Evidence-based practices - Cook, Bryan G.; Tankersley, Melody; Landrum, Timothy J. (Advances in learning and behavioral disabilities, 2013)
This volume focuses on evidence-based practices (EBPs) , supported, sound research studies documenting their effectiveness with a target population. As such, EBPs have significant potential to improve the outcomes of learners with learning and behavioral disorders. However, a number of obstacles exist in identifying, conceptualizing, adopting, and maintaining EBPs that have prevented educators from realizing their potential benefits. The chapters in this volume address many of these issues, with the goal of improving stakeholders? ability to identify and implement EBPs. Chapters discuss the following topics: appraising systematic evidence-based reviews, using single-subject research to identify EBPs, legal issues, implementation fidelity and EBPs, guidelines for implementing EBPs, obstacles to implementing EBPs, teacher preparation and EBPs, EBPs for learners with learning disabilities, EBPs for learners with behavioral disabilities, EBPs for learners with autism spectrum disorders, EBPs in early childhood special education, EBPs in special education in Australia.